Idiopathic hypopharyngeal perforation presenting as supraglottitis and parapharyngeal abscess: case report and literature review. Issue 1 (11th January 2022) - Woodun, Heerani; Woodun, Heyrumb; Sethi, Neeraj; Simons, Anthony
Abstract: A 75-year-old healthy male reported odynophagia and severe neck pain with radiation to chest and shoulders. Cardiac causes were excluded. After re-presenting with dysphonia and complete dysphagia, he was treated for supraglottitis. Imaging showed a left parapharyngeal and retropharyngeal space abscess with mediastinal emphysema. Progressive emphysema prompted contrast swallow test followed by left neck exploration and pan-endoscopy, which confirmed mucosal hypopharyngeal perforations. Histopathology reported inflammation. Autoimmune and gastroenterological aetiologies were excluded. Following conservative management, healing was demonstrated on repeat pan-endoscopy. Two months' follow-up imaging showed complete resolution. Spontaneous hypopharyngeal perforation, atypical of Boerrhave's syndrome and without risk factors (iatrogenic, oesophageal disease and foreign body ingestion), is rare and often misdiagnosed, including masquerading as supraglottitis. Nasoendoscopy should be complemented by radiological imaging. Presence of deep neck space collections and surgical emphysema should prompt diagnostic pan-endoscopy. Although most rupture cases require surgery, conservative management of hypopharyngeal perforations can be considered when clinically appropriate.